"Empty Spaces" in Modern Cultural Landscapes Structure: Identification for the Sake of Socio-Economic Stability (Global Journal of Human-Social Science, 2019)
Cultural landscapes of the Russian Arctic remind a palimpsest where historical spatial fragments are being combined with modern. Complex spatial structure of cultural landscapes in populated regions, in several cases, promote delusion of "empty spaces" existence, i.e., territories not fashioned by some cultural group and thus free for new economic development. Involvement of such territories in modern economic development may cause loss of traditional economy incomes for the indigenous population, as well as cultural heritage and socioeconomic conflicts. Humanitarian geography approaches were used to define cultural landscapes, demonstrate their different patterns in the Russian Arctic. The goal of this study is to reveal the origin of "empty spaces" appearance in the Russian Arctic and demonstrate the importance of cultural landscapes studies to identify and characterize them for the sake of socioeconomic stability.
Keywords: cultural; landscape; Arctic; indigenous; management; mapping